Effect of motorcycle helmet types on head injuries: evidence from eight level-I trauma centres in Taiwan - Carlos Lam; Bayu Satria Wiratama; Wen-Han Chang; Ping-Ling Chen; Wen-Ta Chiu; Wafaa Saleh; Chih-Wei Pai (BMC, 2020)
Abstract Background Motorcycle full-coverage helmet use may reduce fatalities and head injuries. Methods This retrospective cohort study extracted injury data from eight level-I trauma centres in Taiwan and performed a questionnaire survey to investigate injuries sustained by motorcyclists for the period between January 2015 and June 2017. Results As many as 725 patients participated in the questionnaire survey and reported their helmet types or phone use during crashes. The results of multivariate logistic models demonstrated that nonstandard helmet (half or open-face helmet) use was associated with an increased risk of head injuries and more severe injuries (injury severity score ≥ 8). Drunk riding and phone use appeared to be two important risk factors for head injuries and increased injury severity. Anaemia was also found to be a determinant of head injuries." Conclusions Compared to full-coverage helmets, nonstandard provide less protection against head injuries and increased injury severity among motorcyclists.